Evaluating the impact of different furrow irrigation methods on onion bulb yield and water productivity The case of Hadero Tunto district, Southern Ethiopia - Habtewold, Markos; Mengist, Demeke (Ethiopian Journal of Science and Technology, 2025)
The aim of this study was to evaluate the effectiveness of different furrow irrigation methods on bulb yield and water productivity. The experiment was conducted in farmers' fields using a Randomized Complete Block Design, with three treatment levels and five replications. The irrigation methods tested included Alternate Furrow Irrigation (AFI), Fixed Furrow Irrigation (FFI), and Conventional Furrow Irrigation (CFI). The results indicate that furrow irrigation methods significantly influence bulb diameter, yield, and water productivity. The harvested bulb yields were 10.26 t/ha for AFI, 10.32 t/ha for CFI, and 9.36 t/ha for FFI. The maximum water productivity values were 4.8 kg/m³ for AFI and 4.1 kg/m³ for FFI, both achieved with a consistent seasonal crop water requirement of 228.3 mm. In contrast, the CFI method yielded a minimum water productivity of 2.26 kg/m³, with a total applied water depth of 456.6 mm. A partial budget analysis revealed the following net returns: 682,020 ETB/ha for AFI, 560,500 ETB/ha for FFI, and 678,540 ETB/ha for CFI. The benefit-cost ratios were highest for AFI at 12.03, followed by CFI at 10.52, and FFI at 9.89. Based on these findings, we recommend the Alternate Furrow Irrigation method for enhancing onion bulb yield and water productivity, particularly in water-scarce regions with similar agroecological conditions.